A new species of Thysanoptyx Hampson, 1894 from India (Lepidoptera: Erebidae: Arctiinae) - Singh, Navneet; Joshi, Rahul; Kirti, Jagbir Singh; Volynkin, Anton V. (Zootaxa, 2017)
The genus Thysanoptyx Hampson, 1894 is a member of the subtribe Lithosiina, tribe Lithosiini (Arctiinae). It was described as a monotypic genus for Lithosia tetragona Walker, 1854 from Silhet [Sylhet], [Bangladesh].Hampson (1900) treated Thysanoptyx as a synonym of Eilema Hübner. Daniel (1954) placed it under Lithosia Fabricius, whereas Birket-Smith (1965) treated it as a junior subjective synonym of Teulisna Walker. Later, Kishida (1993) considered Thysanoptyx Hampson as a valid genus. Fang (2000) reported four species from China: Thysanoptyx tetragona (Walker, 1854), T. fimbriata (Leech, 1890), T. signata (Walker, 1854), and T. brevimacula (Alphéraky, 1897). However, the male genitalia of T. tetragona figured by Fang (2000) belong to a probably new species (Singh, pers. obs.). Holloway (2001) considered four species, Thysanoptyx tetragona, T. oblonga (Butler, 1877), T. sordida (Butler, 1881), and T. incurvata Wileman & West, 1928 from Oriental region. Kirti & Singh (2015) described a new species, T. pseudotetragona Joshi, Singh & Kirti from South India (Kerala) and reported T. incurvata for the first time from India. However, the new reporting of T. incurvata seems to be incorrect (see the remark below). Recently, Volynkin & Dubatolov (2017) subdivided Thysanoptyx into five species groups: tetragona species group, oblonga species group, sordida species group, signata species group, and fimbriata species group, with the description of two new species: T. indosinica Volynkin & Dubatolov, 2017 from Thailand, Cambodia and Vietnam and T. mirifica Volynkin & Dubatolov, 2017 from Vietnam. At present the genus comprises 10 valid species distributed from China, Taiwan to India and South East Asia.